Japanese Encephalitis (JE): A curse for people living in Uttar Pradesh, India - Jay Prakash Patel; Kusum Verma; Vijeta Singh (Journal of Vaccines and Immunology - Peertechz Publications, 2021)
Japanese Encephalitis (JE) follows due to viral infection that directly affects brain leading to coma and finally death. JE which finally leads to Acute Encephalitis Syndrome (AES) have been creating devastation in eastern Uttar Pradesh for decades. The Gorakhpur in Uttar Pradesh is the epicenter of encephalitis induced deaths and the disease mostly affect its rural areas. However, Maharajgang, Sant Kabir Nagar, Basti, Kushinagar, Siddharth Nagar, Deoria and Mau are the most affected districts in the state. Independent figures put the toll around 50,000 as many kids die without reaching hospital. Every year, in rainy season the condition is worst for children in Uttar Pradesh. The Japanese Encephalitis Virus (JEV) is generally spread by mosquitoes, specifically those of the genus Culex. Pigs and wild birds serve as reservoir for the JEV. Encephalitis can be air or water borne, the result of a mosquito bite or spread by ticks. The initial symptoms are fever, cold or headache. However, it becomes life threatening only when it crosses the blood and brain barrier. There is no full cure of the disease; however, it can only be treated by vaccination to some extent. Prevention includes control of the vector mosquitoes of JEV by fogging with ultra-low levels of insecticides and by raising the immunity in children by vaccination. There are three types of vaccines has been used in large scale. In India, the JE vaccination was launched during 2006. Recently Shri Yogi Adityanath (Chief Minister, Uttar Pradesh) government has launched a massive encephalitis vaccination program during 2017-18 which is a positive hopeful step towards saving the lives of several innocent people of our country.